The Etymological Path to Moral Meaning: Adam and the Names = ālmnhāǧ āltāʾṯīlī ūtāʾṣīl ālmʿnā ālāʾḫlāqī: āʾādm ūālāʾsmāʾ - Masri, Ghassan el (Journal of Islamic ethics, 2021)
Abstract This paper advances the claim that an investigation into the significance of Qurʾānic terms must consider the semantic etymology of the elements under investigation, especially terms that have developed into technical concepts in Islamic theology and philosophy like the ethical variety investigated in this volume. The present article will give some of the salient reason for this imperative and demonstrate the value of semantic etymology in understanding the anthropological dimensions of theological concepts. Semantic etymology, the practice of uncovering the ‘original’ imposition of a word-thing relation (aṣl al-waḍʿ) by deducing the meaning of a word from the meaning of other words sharing the same lexeme was more than a descriptive linguistic science in the Arab-Islamic tradition. In late antiquity the Greek and Latin science of etymologia, like the Arabic ishtiqāq al-maʿná (later ʿilm al-waḍʿ), was a fully-fledged instrument of conceptual analysis for the reader and a powerful tool of discursive authority for both author and reader. Semantic etymology offers an account, not only of the original word-thing relation, but also the essential nature of the object. In our current moment in the history of philosophy where ‘essences’ and ‘essential qualities’ have lost almost all currency, the article opens the door for a reconsideration of the worth of ‘etymologies’ as sound and useful anthropological and philosophical objects of analysis.